The evolution of mitral valve prolapse: insights from the Framingham Heart Study - Niu, Zhaozhuo; Chan, Vincent; Mesana, Thierry; Ruel, Marc (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
The Framingham Heart Study group has described the non-diagnostic variants may evolve into mitral valve prolapse over time. These non-diagnostic variants include minimal systolic displacement, and abnormal anterior coaptation which is measured on surface echocardiography. Computed tomography and cardiac magnetic resonance imaging are evolving and can assess the degree of mitral regurgitation (MR); imaging techniques aside, genetic and proteomic detection of mitral prolapse is also evolving. However, the genetic basis for mitral prolapse is complex and likely involves multiple genetic loci. The same is also true for work determining possible biomarkers associated with mitral prolapse. The present study may be useful in counseling patients with a family history of mitral prolapse. Registry data is therefore of paramount importance in providing unbiased insight into this common disease.